Adopting generative AI tools : A case study on the preparedness of employees and possible implementation barriers in MNCs - Přecechtěl, Filip (2025)
The advent of generative AI tools like ChatGPT has sparked a significant surge in AI interest and investment, pressuring MNCs to integrate these technologies and upskill their workforce. This study investigates the primary barriers MNCs face in adopting generative AI and assesses the AI literacy of their employees. Using a quantitative methodology with data from 113 knowledge workers, the research categorises and ranks AI adoption barriers by importance, removal difficulty, and optimal implementation sequence, while also evaluating current AI literacy levels. Findings indicate that employees generally possess an above-average level of AI literacy, though specific weaknesses exist in identifying AI-based applications and differentiating AI from human communication, particularly among women and older workers. Crucially, the research identifies security, data integrity, potential misuse, ethical considerations, and regulatory alignment as critical initial barriers that companies must address through strategic planning and leadership support. The study concludes with a roadmap for companies to navigate AI adoption, emphasising the removal of key barriers in a prioritised sequence and the continuous development of AI literacy to fully leverage generative AI's potential.